ACESSO À JUSTIÇA E CUSTAS PROCESSUAIS: Análise das decisões judiciais nas Varas Cíveis da Comarca de São Luís - MA, nas demandas de consumo no período de 2012 a 2016. - MILHOMEM, Maria José Carvalho de Sousa (2017)
The objective of this research was to analyze access to justice as a fundamental principle of guaranteeing the citizen to the Judiciary, even when unable to bear the burden of procedural expenses, under the terms of current Brazilian legislation, analyzing free justice and free legal aid. To this end, the theoretical framework "the waves of access to justice" was used, especially the third wave of the access to justice movement developed by Cappelletti; Garth, who is concerned not only with assistance to the poor and diffuse rights and But rather how to put them into effect, evaluating the tendencies of reform of the system that extends the "approach to access to justice". Thus, first, historical and sociological elements are presented to present an evolutionary concept of free justice as one of the corollaries of access to justice, through the basic rulers of the Constitution of the Republic, of infraconstitutional legislation, punctuating, in addition, the methods of research, the methodological assumptions and assumptions. It is necessary to demonstrate access to justice as a fundamental right and exercise of citizenship, listing the difficulties of the jurisdiction in the search for their rights in the face of the high value of procedural costs. It is also necessary to analyze the arguments of the judicial decisions on the rejection of the gratuitousness of justice, evaluating the jurisprudential tendencies of the TJ / MA, regarding the exemption of costs.